DNA-Binding Proteins Regulating pIP501 Transfer and Replication - Grohmann, Elisabeth; Goessweiner-Mohr, Nikolaus; Brantl, Sabine (Frontiers in Molecular Biosciences, 2016)
pIP501 is a Gram-positive broad-host-range model plasmid intensively used for studying plasmid replication and conjugative transfer. It is a multiple antibiotic resistance plasmid frequently found in clinical Enterococcus faecalis and Enterococcus faecium isolates. Replication of pIP501 proceeds unidirectionally by a theta mechanism. The minimal replicon of pIP501 is composed of the repR gene encoding the essential rate-limiting replication initiator protein RepR and the origin of replication, oriR, located downstream of repR. RepR is similar to RepE of related streptococcal plasmid pAMβ1, which has been shown to possess RNase activity cleaving free RNA molecules in close proximity of the initiation site of DNA synthesis. Replication of pIP501 is controlled by the concerted action of a small protein, CopR, and an antisense RNA, RNAIII. CopR has a dual role: It acts as transcriptional repressor at the repR promoter and prevents convergent transcription of RNAIII and repR mRNA (RNAII), thereby indirectly increasing RNAIII synthesis. CopR binds asymmetrically as a dimer at two consecutive binding sites upstream of and overlapping with the repR promoter. RNAIII induces transcriptional attenuation within the leader region of the repR mRNA (RNAII). Deletion of either control component causes a 10- to 20-fold increase of plasmid copy number, while simultaneous deletions have no additional effect. Conjugative transfer of pIP501 depends on a type IV secretion system (T4SS) encoded in a single operon. Its transfer host-range is considerably broad, as it has been transferred to virtually all Gram-positive bacteria including filamentous streptomycetes and even the Gram-negative Escherichia coli. Expression of the 15 genes encoding the T4SS is tightly controlled by binding of the relaxase TraA, the transfer initiator protein, to the operon promoter, which overlaps with the origin of transfer (oriT). The T4SS operon encodes the DNA-binding proteins TraJ (VirD4-like coupling protein) and the VirB4-like ATPase, TraE. Both proteins are actively involved in conjugative DNA transport. Moreover, the operon encodes TraN, a small cytoplasmic protein, whose specific binding to a sequence upstream of the oriT nic-site was demonstrated. TraN seems to be an effective repressor of pIP501 transfer, as conjugative transfer rates were significantly increased in an E. faecalis pIP501ΔtraN mutant.